In silico study of bone tissue regeneration in an idealised porous hydrogel scaffold using a mechano-regulation algorithm - Feihu Zhao (Biomechanics and Modeling in Mechanobiology, 2018)
Mechanical stimulation, in the form of fluid perfusion or mechanical strain, enhances osteogenic differentiation and overall bone tissue formation by mesenchymal stems cells cultured in biomaterial scaffolds for tissue engineering applications. In silico techniques can be used to predict the mechanical environment within biomaterial scaffolds, and also the relationship between bone tissue regeneration and mechanical stimulation, and thereby inform conditions for bone tissue engineering experiments. In this study, we investigated bone tissue regeneration in an idealised hydrogel scaffold using a mechano-regulation model capable of predicting tissue differentiation, and specifically compared five loading cases, based on known experimental bioreactor regimes. These models predicted that low levels of mechanical loading, i.e. compression (0.5% strain), pore pressure of 10 kPa and a combination of compression (0.5%) and pore pressure (10 kPa), could induce more osteogenic differentiation and lead to the formation of a higher bone tissue fraction. In contrast greater volumes of cartilage and fibrous tissue fractions were predicted under higher levels of mechanical loading (i.e. compression strain of 5.0% and pore pressure of 100 kPa). The findings in this study may provide important information regarding the appropriate mechanical stimulation for in vitro bone tissue engineering experiments.